Effect of work:rest cycle duration on fluctuations during intermittent exercise. Issue 1 (2nd January 2017) - Combes, Adrien; Dekerle, Jeanne; Bougault, Valérie; Daussin, Frédéric N.
ABSTRACT: The succession of on-transient phases that induce a repetition of metabolic changes is a possible mechanism responsible for the greater response to intermittent training (IT). The objective of this study was to quantify fluctuations during intermittent exercise characterised by the same work:rest ratio, but different durations and identify which duration leads to the greatest fluctuations. Ten participants (24 ± 5 years; : 42 ± 7 mL·min −1 ·kg −1 ) performed (1) an incremental test to exhaustion to determine peak work rate (WRpeak ) and oxygen uptake ( ), (2), and three 1 h intermittent exercises alternating work period at 70% WRpeak with passive recovery period of different 1:1 work:recovery duty cycles (30 s:30 s, 60 s:60 s, 120 s:120 s). response analysis revealed differences in the fluctuations across the intermittent conditions despite an identical total energy expenditure. The sum of the cycle's nadir-to-peak differences (ΣΔ ) and the oxygen fluctuation index (OFI) were both greater in the 60 s:60 s condition (ΣΔ : +38% ± 13% and +19% ± 18% vs. 120 s:120 s and 30 s:30 s, P < 0.05; OFI: +41% ± 29% and +67% ± 62% vs. 120 s:120 s and 30:30 s, P < 0.05). fluctuation analysis was successful in identifying the intermittent condition associated with the greatest disturbances: the 60 s:60 s duty cycle induces more fluctuations. The present findings also demonstrate that the selection of the duty cycle duration for submaximal intermittent exercise (70% of WRpeak ) prescription is of interest to produce high fluctuations.